Pendidikan Karakter melalui Tradisi Ngebuyu sebagai Kearifan Lokal Masyarakat Lampung Pesisir - Nur Indah Lestari; Rinaldo Adi Pratama; Yusuf Perdana3; Sumargono Sumargono (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
The purpose of this study was to determine the character education of the Lampung Pesisir community through the tradition of ngebuyu local wisdom. This research method is a type of qualitative research using an ethnographic approach that describes the local culture of the Lampung Coastal Kalianda community, namely Ngebuyu. The results show that local culture contains character education values ​​that are important to be transformed to the younger generation. One such culture is the Negbuyu tradition. The Ngebuyu tradition is a tradition carried out by the people of Coastal Lampung in the Kalianda area, South Lampung Regency. The Lampung Coastal community or commonly referred to in the local language as 'Ulun Lampung Saibatin' has a ritual in welcoming the birth of a baby, the ritual or tradition is called Ngebuyu. The conclusion of the research on the character education of the ngebuyu tradition by internalizing cultural values ​​in history learning can attract students' interest in learning history and make history learning more meaningful. Keywords: Character Education, Ngebuyu Tradition, Local Wisdom